A National Survey Evaluating the Impact of the COVID-19 Pandemic on Medical Students Pursuing Careers in Neurosurgery. (16th November 2020) - Garcia, Roxanna; Reynolds, Rebecca; Weiss, Hannah; Chambless, Lola B; Lam, Sandi; Dahdaleh, Nader S; Rosseau, Gail L
Abstract: INTRODUCTION: The COVID-19 pandemic has significantly disrupted medical students (MSs)' educational experience, and this has unclear implications for those pursuing careers in neurosurgery. METHODS: A cross-sectional, online survey was distributed to MSs and foreign medical graduates (FMGs) residing in the United States who are considering or pursuing careers in neurosurgery. Descriptive statistics comparing MS years were performed. RESULTS: A total of 379 respondents from 67 medical schools completed the survey. Across all participants, 92% (n = 347) have stopped in-person didactic education, and 43% (n = 161) have experienced basic science and 44% (n = 167) clinical research delays. Sixty percent (n = 227) cite a negative impact on academic productivity. Among first year medical students (MS1s), 18% (n = 17) are less likely to pursue a career in neurosurgery. Over half of MS2s and MS3s are likely to delay taking the United States Medical Licensing Examination (USMLE) Steps I and II. Among MS3s, 77% (n = 91) report indefinite postponement of sub-internships, and 43% (n = 53) are unsatisfied with communication from external programs. Many MS4s (50%, n = 17) are graduating early to participate in COVID-19-related patient care. The top student-requested support activities included access to student-focused educational webinars and studentfocused sessions at upcoming neurosurgical conferences. CONCLUSION: Medical students pursuing careers in neurosurgery have unique academic, career, and personal challenges secondary to the pandemic. These challenges may become opportunities for new initiatives guided by organized neurosurgery and residency programs.